ALTERNATIVAS FORRAGEIRAS PARA SISTEMAS DE PRODUÇÃO DE OVINOS DE CORTE NO BIOMA CERRADO NO PERÍODO DA SECA - Juliana Caroline Santos Santana (2025)
Lamb farming has great growth potential in Brazil and worldwide but lacks targeted information on proper forage management to maximize production. The objective of this study was to evaluate forage production, canopy structure, and the nutritional value of Brachiaria and Panicum cultivars, as well as to assess the effects of these grasses on the health, behavior, and productive performance of lambs in the Brazilian Cerrado. The experimental design was randomized blocks with five cultivars from the Brachiaria (Marandu, BRS Ipyporã, and BRS Paiaguás) and Panicum (BRS Quênia and BRS Tamani) genera, with two replications. The lambs, of undefined breed, were managed under continuous grazing with stocking rate adjustment and daily protein supplementation of 1% of body weight. The lambs were evaluated considering animal health parameters: body weight, FAMACHA©, body condition score (BCS), eggs per gram of feces (EPG), coproculture, average daily gain (ADG), and ingestive behavior. The grasses were analyzed for forage mass (FM), nutritional value, and litter dynamics. The cultivars significantly influenced (p